"A waste of time without patients": The views of patient representatives attending a workshop in evidence‐based practice. Issue 3 (25th June 2018) - Austvoll‐Dahlgren, Astrid; Johansen, Marit
Abstract: Background: Shared decision‐making is a central element of evidence‐based practice (EBP). Training in EBP has traditionally focused on providers, but there is an increasing interest in developing such educational resources for patients. The aim of this study is to explore the views of patient representatives attending a workshop in EBP. Methods: We conducted three focus groups with participants attending EBP workshops in 2013, 2014, and 2015. We used the framework method for content analysis. We reviewed the transcribed interviews independently and assigned initial codes and final categories to the transcriptions. We created an analytical framework and a flow diagram to visualize the category hierarchy and the relationship between categories. Results: We identified two main themes; "How to facilitate training in evidence‐based practice for patients, " and "Outputs of training in evidence based practice for patients." Training in EBP for patient representatives "should reflect the principles EBP, " and include interaction with both health professionals and other representatives. The educational needs of representatives are much the same as those of health professionals, and the training should therefore be "on a par with professionals." The relevance of such training may depend on the representatives' mandate, and costs might be an important barrier. Important outputs of such training include "becoming a knowledge manager, " "enabling participation and informed decisions" and "re‐defining the patient representatives' role." Conclusions: The findings of this study suggest that training in EBP is attractive to patient representatives with outputs perceived important. Organizers should consider the principles of EBP when planning such training.